PENERAPAN ENTERPRISE RESOURCE PLANNING DALAM MENUNJANG SISTEM INFORMASI MANAJEMEN PADA MADRASAH TSANAWIYAH DARUL – HIKMAH BANDUNG SARI - Akhmad As Sakhaf; Achmad Imam Agung; Tanhella Zein Vitadiar; Muhmmad Fatkhur Rizal (Kampus Akademik Publiser, 2024)
Madrasah Tsanawiyah (MTs) Darul – Hikmah is one of the private schools founded by KH. Abu Bakar and has a level of education equivalent to the level of first secondary school (SMP). In supporting the management performance of MTs Darul - Hikmah Bandung Sari in providing information on every kind of management of madrasah, it is necessary to have an Enterprise Resource Planning (ERP) system which functions as an integration system on every type of madrasah’s management. From this system, each type of administration can exchange the information needed as well as to rejuvenate the data management and decision-making quickly. This ERP system was created by using the SISFO web-based school framework, SISFO School is a web-based school management monitoring system which manages and integrates every school management system including the principal, the enterprise, the curriculum, the student affair, the facility, the teacher and the student. This ERP is provided by using the Waterfall method. Waterfall is one of the application methods of the System Development Life Cycle method, which emphasizes sequential and systematic phases such as waterfalls. With phases of needs analysis, system design, implementation, system testing, and maintenance. This ERP application has a system requirement to manage each of management data including the principal, administration, curriculum, student affair, educator, teacher, and student. The process of testing the system uses a black box with a